Implementasi Sistem Indikasi Kebakaran Menggunakan Mikrokontroler Dalam Smarthome - Lazuardy Muhammad (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In urban environments Fires are a frequent occurrence of the main causes of urban fires being short-circuits and gas leaks. Gas leaks in homes generally occur in the kitchen. So needed a system in order to read indication if there is a fire. MQTT is a communication protocol on IoT that implements publish and subscribe. Sensors that become publishers are fire and smoke sensors while the buzzer becomes a subscriber. MQTT is used because it is suitable for communication between machines, can operate at low power and can send messages very quickly. Fire detection system is implemented by connecting all microcontroller with sensor so it can transmit data. The sensor reads data from the environment if the data in the read exceeds the parameters it will cause buzzer to sound. Testing the system is done by calculating the system time in sending data from the sensor to the buzzer and can display data directly and graphics, setting the buzzer and set the parameters for the sensor. The results of the test system can read and display data in real time and change it in the form of graphics and speed of sending the sensor from the beginning until the buzzer buzzer is 1 second.